2010
DOI: 10.1258/la.2010.010030
|View full text |Cite
|
Sign up to set email alerts
|

Defining a longitudinal survival model to examine forced treadmill running as a countermeasure for diet-induced weight gain

Abstract: Diet-induced weight gain increases disease risk via disruption of the innate immune system. Flow cytometry is commonly used to assess the immune system; however, in mice such measurements traditionally require terminal procedures and tissue collection to generate sufficient sample. The present study refined an existing flow cytometry method to reduce the number of mice needed to longitudinally measure monocytes. CD-1 male mice were randomly assigned to one of the three groups: DS (diet-induced weight gain þ se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Within the exercised group, there was a positive correlation between the increase in both BMI and glycemia accompanying the carbohydrate-rich and fat-rich diet (compared to the standard diet). The sedentary mice showed a greater increase in BMI and glycemia than the exercised animals with the same diets, which is in agreement with the previous reports [ 37 – 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…Within the exercised group, there was a positive correlation between the increase in both BMI and glycemia accompanying the carbohydrate-rich and fat-rich diet (compared to the standard diet). The sedentary mice showed a greater increase in BMI and glycemia than the exercised animals with the same diets, which is in agreement with the previous reports [ 37 – 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…We have previously demonstrated that mice that are group-housed (groups of five) and restricted from structured physical activity have greater weight gain than normal growth rates. 10,11 Consistent with reports from other laboratories, we have also demonstrated that extremely high-fat diets (60% of calories from fat) result in excessive weight gain above normal growth. 10 Neither our laboratory nor others have specifically compartmentalized weight gain into lean and fat masses.…”
supporting
confidence: 91%
“…important because increased fat mass underlies the metabolic changes that result in obesity-associated diseases. 10,11,14 For example, increases in fat mass are associated with decreased production of adiponectin as well as increased production of leptin and proinflammatory cytokines (TNF-a, IL-1b, and IL-6). 15 By controlling for changes in fat mass, we are able to demonstrate that the feeding pattern described in this report mirrors body fat distributions in obese humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations